Gastro-omental free flap for reconstruction of tongue defects. (August 2018) - Vidhyadharan, Sivakumar; Thankappan, Krishnakumar; Janarthanan, Ramu; Balasubramanian, Deepak; Sharma, Mohit; Mathew, Jimmy; Sudheer, Othiyil Vayoth; Iyer, Subramania
Highlights: Novel technique of free gastro-omental flap for tongue reconstruction. Prospective case series of 9 cases of tongue defects. The flap provided a secretory mucosal surface, in post-radiotherapy patients. Laparoscopic harvest minimized donor site morbidity. Speech and swallowing outcome was good. Abstract: Objectives: The purpose of this paper is to report the technique and outcomes of the use of gastro-omental free flap reconstruction in glossectomy defects. Materials and Methods: This is a prospective case series of 9 patients of tongue squamous cell carcinoma, who underwent either subtotal or partial glossectomy and reconstruction with gastro–omental free flap. The flap anatomy, surgical technique and the outcomes including the swallowing and speech are presented. Results: Five patients underwent partial glossectomy and 4 had sub-total glossectomy. The median age was 43 years; and the median follow up was 11.4 months. Laparoscopic harvest was done in 8 patients. There was one flap loss. Seven patients underwent postoperative radiotherapy. Functional evaluation was done in 5 patients who were disease free. Four could tolerate soft diet orally, one patient was on liquid to pureed diet. Speech was intelligible in 4. None of the patients had any complications related to laparotomy or laparoscopy. Conclusion: Gastro-omental flap provided a secretory mucosal surface and was beneficial in the saliva depleted patients post radiotherapy. The laparoscopic harvest of this flap has minimized donor site morbidity. One patient had a flap loss. Two patients reported superficial ulcerations on the surface, one of them had to undergo surgical debulking to correct it while the other healed with conservative measures. Speech and swallowing outcomes of the reconstructed tongue was good, especially in patients with partial glossectomy. The reconstructed gastric mucosal flaps tolerated the adjuvant radiation well.